2020
DOI: 10.1007/s00170-020-05199-9
|View full text |Cite
|
Sign up to set email alerts
|

Additive manufacturing of metal-bonded grinding tools

Abstract: Grinding tools with superabrasive grains can be manufactured from different bond materials. In several industrial applications, metallic bond systems are used. In general, these show good grain retention and offer a high thermal conductivity, when compared to the other widely used bond types such as vitrified and resin bonds. One drawback of the metallic bond is the lack of pores in the grinding layer. This is caused by the manufacturing processes that are typically used, like brazing or hot pressing. These ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Pore structure is an important feature of abrasive tool, its purpose is to increase the chip holding space and dressing ability of abrasive tool, and improve self-sharpening. 31 Comparing the pore structure of the gel abrasive tool and the hot-pressing abrasive tool, it can be seen from Fig. 12 that a large number of capillary pores are formed on the surface of the gel abrasive tools.…”
Section: Preparation and Performance Test Of Gel Abrasive Toolsmentioning
confidence: 99%
“…Pore structure is an important feature of abrasive tool, its purpose is to increase the chip holding space and dressing ability of abrasive tool, and improve self-sharpening. 31 Comparing the pore structure of the gel abrasive tool and the hot-pressing abrasive tool, it can be seen from Fig. 12 that a large number of capillary pores are formed on the surface of the gel abrasive tools.…”
Section: Preparation and Performance Test Of Gel Abrasive Toolsmentioning
confidence: 99%
“…They compared the results of both wheels in terms of wheel loading, wheel wear and surface roughness and concluded that the wheel having coolant channels performed significantly better than the wheel without coolant channels. To address the disadvantage of a metal bond grinding wheel, which is the lack of coolant transportation in the grinding zone, Denkena et al 195 applied the laser powder-based fusion AM method to introduce pores in the metal bond layer of the grinding wheel. Likewise, to increase the amount of cutting fluid in the grinding zone, Li et al 196 fabricated the porous metal bonded grinding wheels having octahedron and honeycomb structures using the Selective laser melting technique.…”
Section: D Printing Of Grinding Wheelsmentioning
confidence: 99%
“…Denkena et al [ 87 ] used the laser powder bed fusion (LPBF) technique to fabricate NiTi diamond composites. Although LPBF is a technique for a large range of metal powders, these types of specimens for use as grinding tools were manufactured for the first time.…”
Section: Application Of Am Technologies In Abrasive Machiningmentioning
confidence: 99%